(untitled) (Research, Society and Development, 2022)
This study aimed to describe, based on the literature, the main care provided to terminally ill patients. This is an integrative literature review. The Health Sciences Descriptors were used for the search: Palliative Care; Health professionals; Intensive care unit; Terminal illness in Portuguese and English was carried out through the following bases: Latin American and Caribbean Literature on Health Sciences, Regional Online Information System for Scientific Journals from Latin America, the Caribbean, Spain and Portugal, Grupo Verde de Agroecologia e Abelhas , Online System of Search and Analysis of Medical Literature. In this way, after the systematic search and application of the inclusion and exclusion criteria, 09 scientific articles were analyzed in the period from 2017 to 2021. The manuscripts allowed us to conclude that the main care performed for terminally ill patients who are in palliative care are: the provision of of basic care to patients who depend on the technical-scientific competence of the team; the use of herbal medicines with medicinal plants; the use of new technologies, as long as they respect ethical precepts, especially aimed at improving the quality of life; and spiritual care that, even if not performed by the team, can be spent as the patient has some belief. It is worth mentioning that despite the findings, there is still a vacuum in the literature with regard to palliative care. Since each manuscript brings a different care. Therefore, it is suggested that new studies be carried out and that they bring a systematization of care, which will facilitate its application.